Atrial Fibrillation in Transient Ischemic Attack Versus Ischemic Stroke: A Swedish Stroke Register (Riksstroke) Study. Issue 10 (October 2016) - Buchwald, Fredrik; Norrving, Bo; Petersson, Jesper
Abstract : Background and Purpose—: Compared with ischemic stroke (IS), the association of atrial fibrillation (AF) with transient ischemic attack (TIA) is less well established. We aimed to assess the proportion of AF in patients with TIA, and these patients' characteristics and secondary preventive treatment in comparison to patients with IS. Methods—: Hospital-based data on TIA and IS events, registered from July 2011 to June 2013, were obtained from the Swedish Stroke Register (Riksstroke). A time-based TIA definition (duration of symptoms <24 hours) was applied. AF was registered as present when previously known or diagnosed at the time of assessment. Results—: AF was present in 2779 of 14 980 (18.6%) patients with TIA and 13 258 of 44 173 (30.0%) patients with IS. The proportion of AF increased with age, reaching 32.9% in TIA and 46.6% in IS patients ≥85 years. Both in TIA and IS, age, hypertension, a history of stroke, and TIA, and being a nonsmoker were associated with the presence of AF. In contrast to IS, AF was less common in female than in male patients with TIA. At discharge, 64.2% of TIA and 50.0% of IS patients with AF were treated with oral anticoagulants. Proportions of AF patients treated with oral anticoagulants decreased substantially with increasing age. Conclusions—: AF is highly prevalent not only in IS but also in TIA patients, with proportions steeply increasing with age. In both TIA and IS, a substantial proportion of patients with AF were discharged without anticoagulant therapy.